Impact of steam cooking on the phytochemical content, antioxidant activity and anticancer activity of three commonly consumed Brassica plants - Yaneenart Suwanwong; Somchai Boonpangrak (Applied Food Research)
Steam cooking is the classical and recommended method for human food due to its simplicity, low cost, and ability to preserve food quality. This study investigated how short-term and long-term steaming affects the phytochemical contents, antioxidant capacities, and anticancer properties of three commonly consumed Brassica vegetables: choy sum, cabbage, and Chinese cabbage. The findings showed that, among 3 vegetables, choy sum possesses the highest amount of key antioxidant substances—including total phenolic content (TPC), total flavonoid content (TFC), and vitamin C (VIT C)—as well as the highest antioxidant activities, while cabbage possesses the highest amount of total glucosinolate content (TGL) and total isothiocyanate content (TIC). Notably, short-term steaming enhanced the antioxidant activities and phytochemical contents across all three vegetables. Long-term steaming resulted in either a slight increase or a decrease in phytochemical content, depending on the types of vegetables and substances tested. Cabbage demonstrated the strongest anticancer activity against a leukemic cell line (U937). However, the effect of steaming on anticancer activity is inconclusive. In summary, this study highlights short-term steaming as an optimal cooking method for maximizing the health-promoting properties of brassica vegetables. These insights may inform culinary recommendations aimed at enhancing the nutritional and biological benefits of a wide range of vegetables.